ХИМИЯДАН ЕСЕПТЕР ШЫҒАРУ ƏДІСТЕМЕСІНІҢ КЕЙБІР АСПЕКТІЛЕРІ - Таурбаева, Г.У. (My University, 2019)
Аннотация Химиядан есептер шығару білім алушыларға теориялық білімді тереңдетуге, оны стандартты емес жағдайда пайдалануға, математикалық ой-өрісін дамытуға мүмкіндік бере- ді. Қазіргі кезде оқушыларды əртүрлі деңгейдегі пəндік олимпиадаларға дайындау жұмысы- на орта білім беру мектептерінде көп көңіл бөлінеді жəне бұл дарынды оқушыларды ірік- теуге мүмкіндік береді. Мақалада жұмыс тəжірибемізден байқаған химиялық есептерді шығарудың кейбір жалпы бір əдіс-тəсілдері аталып, мысалдар келтірілді. Abstract The educational role of tasks is expressed in the fact that, for example, calculated tasks reveal to students a quantitative aspect of chemistry as an exact science. Tasks are the connection between theory and practice, in the process of solving them, the chemical concepts of substances and pro- cesses are consolidated and improved. Tasks are the connection between theory and practice, the concepts of substances and chemical processes are better assimilated and generalized in the process of solving them. The solution of chemical problems contributes to the realization of the connection of education with life, fosters diligence and purposefulness. The article discusses some general aspects of solving complicated problems in chemistry.
Some aspects of the technique for solving chemistry problems
Keywords: химиялық есептер; газдар қоспасы; орташа молекулалық масса; газдардың салыстырмалы тығыздығы; сhemical problems; gas mixtures; average molecular weight; relative density of gases